Teaching how to fish: strategic practices in an entrepreneurial non-profit organization - da Cunha Pimentel de Meira, Alexandra Esperança; Meyer Jr., Victor; Pascuci, Lucilaine (REBRAE, 2014)
The aim of this study is to analyze the strategic practices developed by a Brazilian nonprofit organization, which focuses on the promotion of social entrepreneurship at the bottom of the pyramid. The major goal of the study is to focus on the strategies of its project managers. The study is based on the concepts of Salamon (2003) and Moore (2000) and the role played by the nonprofit organization in the same manner that entrenches the theories of complex adaptive systems and the loosely coupled systems. It has also highlighted the use of strategy-as-practice as a theoretical basis to better understand the social actions. It is a case study of a qualitative nature. Data were collected from analysis of documents, non-participant observation and interviews. Data analysis revealed that project managers played a critical role as strategists. In their social practices they combine experience, sensemaking, interactions, decision making and knowledge together with neutrality and autonomy for action. The results revealed that the number of micro-entrepreneurs who benefited from the projects has grown significantly during the period of the study. Likewise, the income of these micro-entrepreneurs and that of their families has displayed a steady increase. The conclusion indicates that strategic practices carried out by project managers have brought social value to micro-entrepreneurs and contributed significantly to the achievement of the organization`s goals.